2012
DOI: 10.1115/1.4006446
|View full text |Cite
|
Sign up to set email alerts
|

Numerical-Experimental Comparison in the Simulation of Rotor/Stator Interaction Through Blade-Tip/Abradable Coating Contact

Abstract: Higher aircraft energy efficiency may be achieved by minimizing the clearance between the rotating blade tips and respective surrounding casing. A common technical solution consists in the implementation of an abradable liner which improves both the operational safety and the efficiency of modern turbomachines. However, unexpected abradable wear removal mechanisms were recently observed in experimental set-ups as well as during maintenance procedures. Based on a numerical strategy previously developed, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 23 publications
12
125
0
3
Order By: Relevance
“…3. This blade design has been used for the simulation of blade/abradable coating interaction in [3]. It was found that it is particularly sensitive to blade/abradable coating interaction around several critical frequencies.…”
Section: Bladementioning
confidence: 99%
See 2 more Smart Citations
“…3. This blade design has been used for the simulation of blade/abradable coating interaction in [3]. It was found that it is particularly sensitive to blade/abradable coating interaction around several critical frequencies.…”
Section: Bladementioning
confidence: 99%
“…These simulations are carried out based on the strategy presented in [16], that was applied in [3] and is briefly recalled here for the sake of clarity. For a definition of variables see the Nomenclature at the end of this paper.…”
Section: Benchmark Time-domain Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they may lead to blade failure [1] and increased vibratory levels which may damage the structure, a significant amount of work has been dedicated to the understanding of these phenomena as well as the development of strategies for avoiding them. The repetability of such experiments as well as the possibility to obtain accurate results from numerical simulations [2] indicate that the interaction phenomenon is possibly robust. It is thus of great interest to assess the severity of this phenomenon for other types of compressor such as centrifugal compressors, also named impellers.…”
Section: Introductionmentioning
confidence: 99%
“…In this area, recent numerical developments focused on a single blade of axial compressors [2,3]. There is now the need for a general methodology relevant to a large family of structures featuring cyclic symmetry for which such interaction occurrences may arise.…”
Section: Introductionmentioning
confidence: 99%